What is modernity? : writings of Takeuchi Yoshimi - Takeuchi, Yoshimi, 1910-1977; Calichman, Richard (New York : Columbia University Press, 2005)
Regarded as one of the foremost thinkers in postwar Japan, Takeuchi Yoshimi (1910-1977) questioned traditional Japanese thought and radically reconfigured an understanding of the subject's relationship to the world. His works were also central in drawing Japanese attention to the problems inherent in western colonialism and to the cultural importance of Asia, especially China. Takeuchi's writings synthesized philosophy, literature, and history, focusing not simply on Japan and the West but rather on the triangular relationship between Japan, the West, and China. This book, which represents the first appearance of Takeuchi's essays in English translation, explores Japanese modernity, literature, and nationalism as well as Chinese intellectual history. Takeuchi's research demonstrates how Asians attempted to make sense of European modernity without sacrificing their own cultural histories. An authentic method of modernity for Asia, Takeuchi concludes, needs to stress difference and plurality as opposed to the homogenizing force of westernization.
Ways of introducing culture (Japanese literature and Chinese literature II) : focusing upon Lu Xun -- What is modernity? (The case of Japan and China) -- The question of politics and literature (Japanese literature and Chinese literature I) -- Hu Shi and Dewey -- Overcoming modernity -- Asia as method.
Translated from the Japanese.
Print version record.
JSTOR
Keywords: Japan -- Intellectual life -- 1868-; Japon -- Vie intellectuelle -- 1868-; HISTORY; LITERARY CRITICISM -- Asian -- General; Intellectual life; Japan; Since 1868